2019
DOI: 10.54783/japp.v2i3.21
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Reformasi Birokrasi Dan Budaya Kerja Terhadap Kinerja Pegawai Di Rsud Dr. R. Soedjono Selong, Kabupaten Lombok Timur

Abstract: Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh reformasi birokrasi dan budaya kerja terhadap kinerja pegawai di Rumah Sakit Umum Daerah dr. R. Soedjono Selong Kabupaten Lombok Timur Provinsi Nusa Tenggara Barat. Penelitian ini menggunakan metode kuantitatif dengan jumlah responden sebanyak 270 orang pegawai yang diambil memalui teknik stratified random sampling. Hasil penelitian menunjukkan bahwa reformasi birokrasi dan budaya kerja berpengaruh positif dan signifikan terhadap kinerja pegawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In his research, he found that work culture had a significant effect on employee performance (p value <0.05). This means that if the work culture is improved or supported, the increase is stimulated followed by an increase in performance (Suardi et al, 2019).…”
Section: Effect Of Work Culture On Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In his research, he found that work culture had a significant effect on employee performance (p value <0.05). This means that if the work culture is improved or supported, the increase is stimulated followed by an increase in performance (Suardi et al, 2019).…”
Section: Effect Of Work Culture On Performancementioning
confidence: 99%
“…Suardi et al discovered that work culture had a substantial effect on dr. R. Soedjono Selong's performance. This effect implies that if the work culture is changed or supported, it stimulates an improvement in employee performance (Suardi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%